Prediction of cardiovascular events and all-cause mortality using race and race-free estimated glomerular filtration rate in African Americans: the Jackson Heart Study - Wang, Haiping; Cai, Jiahui; Fan, Hao; Diamantidis, Clarissa J.; Young, Bessie A.; Bidulescu, Aurelian (Frontiers in Medicine, 2024)
Background New Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations without a race adjustment were developed to estimate the glomerular filtration rate (eGFR). We aimed to compare the performance of five CKD-EPI eGFR equations, with or without race, in predicting cardiovascular disease (CVD) events and all-cause mortality in Black Americans from the Jackson Heart Study. Methods JHS is an ongoing population-based prospective cohort study of African Americans in the Jackson, Mississippi, metropolitan area. Five CKD-EPI equations were used to estimate GFR at baseline using serum creatinine (Cr) or cystatin C (cys), including 2009 eGFRcr(ASR [age, sex, race]), 2021 eGFRcr(AS [age and sex]), 2012 eGFRcr-cys(ASR), 2021 eGFRcr-cys(AS), 2012 eGFRcys(AS). Endpoints were incident CVD events and all-cause mortality. Cox proportional hazards regression was used to assess the associations between different eGFRs and outcomes adjusting for atherosclerotic risk factors. Harrell’s C-statistics and Net Reclassification Index (NRI) were used to assess the predictive utility. Results Among 5,129 participants (average age 54.8 ± 12.8 yrs), 1898 were male (37.0%). eGFRcr(AS) provided lower estimates and resulting in a greater proportion of participants categorized as CKD than eGFRcr(ASR), eGFRcr-cys(ASR), eGFRcr-cys(AS) and eGFRcys(AS). A median follow-up of 13.7 and 14.3 years revealed 411 (9.3%) CVD incidents and 1,207 (23.5%) deaths. Lower eGFRs were associated with CVD incidents and all-cause mortality. eGFRcr-cys(ASR), eGFRcr-cys(AS) and eGFRcys(AS) were strongly associated with incident CVD events and all-cause mortality than eGFRcr(ASR) and eGFRcr(AS). A significant discrimination improvement was found in C-statistics for predicting incident CVD events and all-cause mortality after adding each eGFR measure to the basic model including atherosclerotic risk factors. Across a 7.5% 10-year risk threshold, eGFRcys(AS) improved net classification of all-cause mortality (NRI: 2.19, 95%CI: 0.08, 4.65%). Conclusion eGFR based on creatinine omit race has the lowest mean and detects more CKD patients in Black population. The eGFRs incorporating cystatin C strengthens the association between the eGFR and the risks of incident CVD and all-cause mortality. Cystatin C-based eGFR equations might be more appropriate for predicting CVD and mortality among Black population.